Nocturnal cerebral hypoxia in obstructive sleep apnoea: a randomised controlled trial - Schwarz, E; Furian, M; Schlatzer, C; Stradling, J; Kohler, M; Bloch, K (European Respiratory Society, 2018)
Cerebral hypoxia may promote cerebral damage in patients with obstructive sleep apnoea (OSA). We investigated whether OSA patients experience nocturnal cerebral hypoxia that is prevented by continuous positive airway pressure (CPAP). OSA patients using CPAP underwent sleep studies including pulse oximetry (arterial oxygen saturation (SpO2)) and near-infrared spectroscopy to monitor cerebral tissue oxygenation (CTO) at baseline and after 2 weeks on either subtherapeutic or therapeutic CPAP according to randomised allocation. Changes in oxygenation at end of the 2-week intervention were compared between groups. Among 21 patients (mean apnoea/hypopnoea index 50.3 events·h−1), OSA recurred in all nine patients using subtherapeutic CPAP and in none of the patients using therapeutic CPAP: mean (95% CI) between-group differences in changes of oxygen desaturation index from baseline to 2 weeks +40.7 (31.1–50.4) events·h−1 for SpO2 and +37.0 (25.3–48.7) events·h−1 for CTO (both p<0.001). Mean nocturnal SpO2 and CTO decreased more in patients using subtherapeutic versus therapeutic CPAP: −2.4 (−3.4–−1.1)% and −3.8 (−7.4–−0.1)%, respectively; both p<0.03. Severe CTO drops ≥13% associated with cerebral dysfunction in previous studies occurred in four out of nine patients using subtherapeutic CPAP, but in none out of 12 patients using therapeutic CPAP (p=0.01). In patients with OSA, CPAP withdrawal resulted in nocturnal cerebral deoxygenation, suggesting a role of cerebral hypoxia in predisposing untreated OSA patients to cerebral damage.